Achmad Mochtar dalam Tragedi Vaksin Maut Romusha 1944-1945 dalam Pemberitaan Koran Asing - Alan Kurnia Jaya; Jarudin Jarudin; Kaksim Kaksim (Pusat Riset dan Inovasi Nasional, 2025)
This thesis discusses the role of Achmad Mochtar, a prominent scientist from Indonesia, in the Tragedy of the Fatal Vaccine in Romusah that occurred during the Japanese military occupation, as reported by foreign press in 1944-1945. The aim of this research is to examine the reputation of Achmad Mochtar, who became one of the best scientists Indonesia has ever had, in facing the Tragedy of the Fatal Vaccine in Romusah, where victims died after being injected with a vaccine contaminated with tetanus toxin. The research uses a historical method with a social reconstruction approach based on data from newspapers such as De Telegraaf and HandelsBlad. The methods used in this paper include the historical method, which consists of data collection (heuristics), source criticism, interpretation, and historiography. The data used are mainly from newspapers like De Telegraaf and HandelsBlad, as well as supporting books and websites such as KITLV and www.delpher.nl/kranten, which have greatly facilitated the author in gathering historical sources related to this paper. This study explains that Achmad Mochtar was a doctor and scientist who strongly opposed the Japanese military occupation and the scenario created by the Japanese military in the Tragedy of the Fatal Vaccine in Romusah in 1944-1945. This research uses data analysis methods to examine foreign press reports related to the tragedy, with a focus on how foreign media depicted Achmad Mochtar’s involvement in the cause of the Tragedy of the Fatal Vaccine in Romusah in 1944-1945 and its impact. The results of this study are as follows: Achmad Mochtar, one of the best scientists Indonesia has ever had, became the subject of intense discussion regarding the tragedy he had to endure, the death of Romusah in 1944-1945. Various foreign newspapers, particularly De Telegraaf and HandelsBlad, focused on reporting the ambitious plans of the Japanese military in the creation of vaccines, which were actually intended by the Japanese military to be developed as biological weapons and tested to observe the effects before being used in the Greater East Asia War, which ultimately resulted in the fatal death of hundreds of Romusah in the Klender camp.